Islamic Republic of Iran : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
Domestic demand continued to grow at rapid rates, despite corrective fiscal and monetary policy measures. Although trade and financial sector reforms advanced and foreign direct investment (FDI) regulations were liberalized, there was less progress in improving the business environment, reducing labor market rigidities, and restructuring and privatizing public enterprises. IMF staff stressed the need for further advances in trade liberalization, improved fiscal management, financial system restructuring, labor market reform, privatization, and elimination of subsidies. The managed float exchange regime remains appropriate for Iran.